Credit crunch of collateral squeeze? An empirical analysis of credit supply of the Finnish local banks in 1990-1992 - Vesa Vihriälä (Bank of Finland, 1996)
The paper examines the determination of bank lending in the early 1990s with the data on 393 savings and cooperative banks. Particular attention is paid to the respective roles of bank capital and costs on the one hand and borrower quality on the other hand.The findings do not support the hypothesis of a general credit crunch caused by capital insufficiency.Some findings suggest, nevertheless, that regulatory pressures and perhaps distractions caused by restructuring may have had a negative effect on lending by the savings banks and some cooperative banks.In addition there is some evidence that weak capital contributed positively to credit growth of some subset of banks in 1992.This moral hazard behaviour differs, however, from that observed in a companion paper for the late 1980s. This time the banks resorting to a "gamble for resurrection" were not the weakest banks in terms of capitalization or credit risks, but more in the middle of the spectrum: not so strong that they could take the full losses associated with non-performing assets and not so weak that regulatory pressures had strongly constrained additional lending to ailing customers.These banks were typically cooperative banks rather than savings banks as in the 1980s.On the other hand, weak borrower quality - measured mainly by the share of non- performing assets - contributed significantly to the low growth and contraction of bank lending in 1991 and 1992.In sum, bank capital was not a major factor in the contraction of lending in the early 1990s but lending was significantly reduced by weak borrower quality.
URN:NBN:fi:bof-20140807202
Keywords: 330; credit crunch; capital crunch; borrower quality; collateral squeeze; bank lending